2001
DOI: 10.1080/mmy.39.1.135.137
|View full text |Cite
|
Sign up to set email alerts
|

Phaeohyphomycosis due toCladosporium cladosporioides

Abstract: Phaeohyphomycosis is a clinical entity caused by dematiaceous fungi. We describe a clinical case of phaeohyphomycosis due to Cladosporium cladosporioides in a 45-year-old white male, apparently healthy, human immunodeficiency virus-negative. The patient was treated with terbinafine for 9 months, with regression of a skin lesion. Three months after discontinuation of the therapy, there was a clinical and mycological relapse. After progression of the disease with inadequate treatment, there was no response to am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Case reports have shown a favorable outcome using azole-based therapies. ITC has shown efficacy in the treatment of superficial infections caused by C. cladosporioides, C. sphaerospermum, and C. oxysporum (8,14,37,(41)(42)(43)(44), while VRC was effective against C. macrocarpum in a brain abscess (17). This agrees with our in vitro data, which demonstrated that the azoles, particularly ITC and PSC, have good activity against Cladosporium species, although VRC displayed variable activity.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Case reports have shown a favorable outcome using azole-based therapies. ITC has shown efficacy in the treatment of superficial infections caused by C. cladosporioides, C. sphaerospermum, and C. oxysporum (8,14,37,(41)(42)(43)(44), while VRC was effective against C. macrocarpum in a brain abscess (17). This agrees with our in vitro data, which demonstrated that the azoles, particularly ITC and PSC, have good activity against Cladosporium species, although VRC displayed variable activity.…”
Section: Discussionsupporting
confidence: 82%
“…Most data are from a few reported clinical cases (7,13,15,41). Our study provides the first in vitro data for a large set of clinical isolates, including several species obtained from diverse anatomical sites and not previously reported from clinical samples.…”
Section: Discussionmentioning
confidence: 93%
“…Cladosporium cladosporioides , which causes reproductive disorders in cows [ 20 ] and phaeohyphomycosis in humans [ 21 ] and giant pandas [ 12 ], was also isolated from the vagina and foreskin samples.…”
Section: Discussionmentioning
confidence: 99%
“…Verrucous plaque in subcutaneous phaeohyphomycosis can also be caused by Cladosporium sphaerospermum (Qiu-Xia et al, 2008). However, C. cladosporioides can cause skin infections in healthy immunocompetent individuals (Vieira et al, 2001) and scalp infections (Sosa et al, 2012). Jayasinghe et al (2017) reported a rare case of unilateral cervical lymphadenopathy due to C. oxysporum in a young adult without any systemic infection (Jayasinghe et al, 2017).…”
Section: Genus: Cladosporiummentioning
confidence: 99%